Capabilities of laser ablation – ICP-TOF-MS coupling for isotopic analysis of individual uranium micrometric particles. Issue 11 (6th September 2018) - Ronzani, Anne-Laure; Pointurier, Fabien; Rittner, Martin; Borovinskaya, Olga; Tanner, Martin; Hubert, Amélie; Humbert, Anne-Claire; Aupiais, Jean; Dacheux, Nicolas
Abstract : Isotopic compositions of individual uranium micrometric particles are measured precisely by means of laser ablation – time of flight ICP-MS coupling. Abstract : Capabilities of laser ablation coupled to a time of flight ICP-MS (' icp TOF', Tofwerk) for direct isotopic analysis of U micrometric reference particles deposited on carbon disks were demonstrated. Thanks to the very high temporal resolution which allows quasi simultaneous measurement of all nuclides, the icp TOF is well-suited for the acquisition of the very short transient signals produced by laser ablation of μm-sized particles. With appropriate corrections of the background due to high peak tailing of the 238 U isotope and selection of signals within the detector's linear range, excellent internal and external precisions (0.2–0.4%) for measurement of the 235 U/ 238 U ratios were obtained in the most favorable cases (same abundances for the two isotopes). These precisions are better than the values reported until now in the literature, even with laser ablation coupled with multi-collector ICP-MS (MC-ICP-MS). For particles from other reference materials with low abundances of 235 U, equal or close to the one of natural U, precisions for 235 U/ 238 U ratio measurements (4–5%) were not as good as the ones reported for MC-ICP-MS, but better than the ones obtained with single collector ICP-MS. Minor isotope ratios ( 234 U/ 238 U and 236 U/ 238 U) were also successfully measured, although with limited precision and accuracy when the abundances of the minor isotopes are very low, in the 10 −5 range. This work shows that laser ablation coupled to ICP-TOF-MS has a great potential for ultra-precise isotope ratio measurements provided that the ablated area contains enough analyte and that abundances between isotopes are of the same order of magnitude.